(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The research was aimed at determining the staining patterns of Peanut agglutinin (PNA) lectin and Ulex europaeus agglutinin I (UEA-I) lectin in postnatal developing (day 1 to 8 weeks) male genital excurrent duct epithelium in mice. Materials and Methods: Lectin staining was performed on testis and epididymis of 1-day-old and 1-, 2-, 3-, 4-, 5-, 6-, and 8-week-old ICR mice. Results: Rete testis epithelia were UEA-I- and PNA-negative at all postnatal ages. PNA lectin unclearly stained the epithelial apical surface in efferent ductules (ED) and ductus epididymis up to 2 weeks, while UEA-I was negative in those epithelia. By contrast, at 3 weeks of age, PNA and/ or UEA-I turned to clearly label epithelia in the excurrent duct system. At 5 weeks, efferent ductules epithelium was UEA-I-negative but strongly PNA-positive; segment I was PNA-negative but faintly UEA-I positive; segment II was weakly PNA-positive but strongly UEA-I-positive; segment III was strongly-PNA- and UEA-I-positive; segment IV was weakly UEA-I-positive but strongly PNApositive; and segment V was faintly UEA-I-positive but strongly PNA-positive. At 5 and 8 weeks (the adult), the staining patterns of PNA and UEA-I lectins were nearly identical. Moreover, an increasing staining intensity was observed in both lectins with the advancement of age until 5 weeks of age. Additionally, it was noted that, with the exception of segment I, the staining intensity of PNA gradually increased while that of UEA-I gradually decreased towards the distal section of the ductus epididymis. Conclusion: Lectin PNA and UEA-I staining, in conclusion, indicated epithelial segments in the male genital duct of mice from the postnatal developing age of 3 weeks, and up until 5 weeks, their staining patterns were nearly identical to those in adults. Adv. Vet. Anim. Res., 11(2): 516-523, June 2024 http://doi.org/10.5455/javar.2024.k801